A Cross Sectional Study Of Postmenopausal Experiences And Self-Care Actions Of Kelantanese Women In Malaysia. - Dhillon, Hardip Kaur; Nik Mahmood, Nik Mohamed Zaki (2004)
Menopause is associated with numerous transient typical and atypical symptoms. It is believed that Asian women suffer more of the atypical .symptoms and fewer, and with lesser severity, the typical psychological and vasomotor symptoms then the western women. This study reports the incidence and nature of menopausal symptoms in Kelantanese women and the self-care action taken by them.